130k views
5 votes
Solve for t:= I only need the answer on this one please

1 Answer

3 votes

The expression is given as,


D=rt

Transpose the terms in order to obtain the expression for 't'.

So we need to eliminate 'r' from the other side.

Divide both sides by 'r',


\begin{gathered} D\cdot(1)/(r)=rt\cdot(1)/(r) \\ (D)/(r)=1\cdot t \\ (D)/(r)=t \\ t=(D)/(r) \end{gathered}

Thus, the required expression will be,


t=(D)/(r)

User Kingnight
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.